1986
DOI: 10.1351/pac198658010105
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic homoconjugation in neutral organic molecules

Abstract: -Although commonly discounted as unimportant, cyclic homoconjugation in neutral organic molecules is actually quite widespread and can often confer unusual properties on the molecules in which it occurs. Several new aspects of this subject are illustrated with compounds synthesized in the author's laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 5 publications
(5 reference statements)
0
30
0
Order By: Relevance
“…4 ppm for the C-10 signal, suggesting a significant through-space orbital interaction, a typical feature of medium-sized cyclic polyolefins. [9] The yield of the epoxides was increased considerably when the irradiation was carried out under a flow of air; however, this did not result in complete conversion. Despite the presumably radical mechanism of this oxidation, the configurations of the epoxides were the same as those of the products obtained by treating zerumbone (1a) and 9-isozerumbone (1b) with peracids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ppm for the C-10 signal, suggesting a significant through-space orbital interaction, a typical feature of medium-sized cyclic polyolefins. [9] The yield of the epoxides was increased considerably when the irradiation was carried out under a flow of air; however, this did not result in complete conversion. Despite the presumably radical mechanism of this oxidation, the configurations of the epoxides were the same as those of the products obtained by treating zerumbone (1a) and 9-isozerumbone (1b) with peracids.…”
Section: Resultsmentioning
confidence: 99%
“…[8] To shed light on this behaviour, and to provide clues of general value for the biological relevance of thiol trapping by electrophilic biologically active agents, we have evaluated the relationship between structure and Michael reactivity in a series of analogues of zerumbone where the cross-conjugated dienone system is modified configurationally and electronically by photochemical isomerization and/or removal of transannular interaction (homoconjugation) with the isolated endocyclic double bond of the medium-sized ring. [9] The cysteamine assay, based on the reaction of thioltrapping compounds with cysteamine (3) in DMSO and phase-switch to CDCl 3 , [6] was used to obtain information on the stoichiometry and regiochemistry of addition, and on the relative reactivities of the analogues.…”
Section: Introductionmentioning
confidence: 99%
“…The classical examples of this are diphenylmethane and its derivatives, for which it was shown that intra‐molecular π‐orbital overlap could occur across the methylene group, mediated by a near‐cofacial arrangement of the two aromatic rings and their close proximity due to the appropriate CCH 2 C bending angle . Such electronic interaction has been termed “ homoconjugation ” (IUPAC) . As shown for diphenylmethane derivatives, homoconjugation and the resulting increased electronic delocalization may lead to the expected red‐shift in absorption and fluorescence spectra …”
Section: Introductionmentioning
confidence: 99%
“…PPM and some methyl‐substituted derivatives have found particular attention recently due to their unexpected photoluminescence behavior, the origin of which is, according to experimental observations and DFT calculations, in line with homoconjugation . Homoconjugation is a rare phenomenon referring to π‐orbitals systems which are conjugated although they are separated by an electronically insulating group . This occurrence can arise under certain geometrical conditions, which are basically present in PPM as schematically illustrated in Scheme (b) .…”
Section: Introductionmentioning
confidence: 99%
“…6 Homoconjugation is a rare phenomenon referring to p-orbitals systems which are conjugated although they are separated by an electronically insulating group. 7,8 This occurrence can arise under certain geometrical conditions, which are basically present in PPM as schematically illustrated in Scheme 1(b). 9,10 Besides, PPM possesses high thermal stability.…”
mentioning
confidence: 99%